Cir-based best-route prediction and adaptive modulation for routing in ofdm-based ad hoc wireless networks - Wong, Wee Sian (Universiti Malaysia Sarawak (UNIMAS), 2008)
In order to facilitate communication within an ad hoc wireless network, a routing protocol is required to route data between nodes. The primary goal of such routing protocol is to guarantee the correct and efficient information exchange between the nodes. In the respect, one of the critical issues to be tackled for achieving routing efficiency is the channel quality among the devices, which may sometimes being ignored in some of the ad hoc wireless routing protocols. Such practice can be a severe shortcoming as the varying channel quality can lead to very poor overall route quality which in turn result in high error rate and low data throughput. %f This research work tries to approach the stated issue from the Physical Layer (PHY) perspective of an Orthogonal Frequency Division Multiplexing (OF[S`M) broadband ad hoc wireless network. It proposes two wireless routing schemes, namely, the Adaptive-All and Adaptive-Select Routing Scheme, for routing data over the OFDM network. The schemes cover the scope of (a) best-route prediction, and (b) adaptive modulation, based on the channel quality, which is measured by its Channel Impulse Response (CIR). The best-route prediction algorithm determines the best route with the least Bit Error Rate (BER) expected. Through the selected best route, adaptive OFDM modulation is performed towards each OFDM sub-channels for data transmission over the route. These schemes are formulated with the objective to improve network performance of an OFDM broadband ad hoc wireless network, through the reduction of BER, and improvement of data throughput. Extensive simulation results show that the proposed schemes achieve the stated goal. As a whole, this research work succeeds in producing two Physical-Layer-based components of ad hoc routing, i. e. the best-route prediction algorithm and the adaptive modulation mechanism, which can be further extended to form a new wireless ad hoc routing protocol, or incorporated into other well-known ad hoc routing protocols, for achieving better routing efficiency in OFDM-based broadband network.